Factors Influencing Financial Reporting Quality in Medan Government: The Moderating Role of Commitment - Rona Lamretta Sinurat; Iskandar Muda; Rina Br Bukit (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to analyze the influence of human resource competence,government internal control systems, and information technology utilization on the quality of financial reports, and to examine the role organizational commitement as a moderating variable in the Medan City Government. Reliable financial reporting quality is essential to ensure transparency and accountability in regional financial management. Therefore, understanding the factors influencing it is crucial. The research employs a quantitative approach using primary data collected through questionnaires distributed to employees involved in the preparation of financial reports in the Medan City Government. The study population consists of 63 Regional Work Units (SKPD) with a total of 210 respondents selected using purposive sampling, including heads of agencies,secretaries,teasurers, and financial administration official (PPK). Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS software.The findings indicate that human resources competence, government internal control sysrems, and information technology utilization have a positive and significant effect on financial reporting quality. Additionally,organizational commitment significantly moderates the influence of these independent variables on financial reporting quality. These results highlight the importance of enchancing human resource competence, strengthening internal control systems, and optimizing information technology utilization, all supported by strong organizational commitment, to produce high-quality financial reports.